Anthropometric and physical fitness traits of four-time World Greco-Roman wrestling champion in relation to national norms: A case study - Mirzaei, B.; Curby, D. G.; Barbas, I.; Lotfi, N. (Journal of Human Sport & Exercise, 2011)
The purpose of the present investigation was to describe the anthropometric and physical fitness traits of a four-time World senior Greco-Roman wrestling champion (age: 24 years, height: 167 cm, weight: 61 kg) in relation to national norms. The anthropometric traits included body weight, height, sitting height, arm-span, and the physical fitness traits included flexibility (sit-and-reach, trunk-and-neck extension and shoulder-and-wrist elevation tests), maximal oxygen uptake (Gas analysis method), muscular endurance (pull-ups and bent-knee sit-ups), muscular strength (bench press, squat), agility (4×9 m shuttle run), speed (40-yd sprint), bilateral visual reaction time and body composition. The major results are as follows: body fat (%): 8.4; body weight (kg): 61; height (cm): 167; sitting height (cm): 89; arm-span (cm): 174; sit-and-reach (cm): 45; trunk-and-neck extension (cm/cm): 0.64; shoulder-and-wrist elevation (cm/cm): 0.54; maximal oxygen uptake (ml/kg·min): 56; pull-ups (reps): 50; bent-knee sit-ups (reps/min): 77; agility (s): 7.6; speed (s): 4.57; bilateral visual reaction time (ms): 229; 1RM weight lifted in the bench press relative to body weight (kg/kg): 1.39 and 1 RM weight lifted in the squat relative to body weight (kg/kg): 1.83. The present study indicated that measures of the squat, speed and agility tests of the subject were higher than Iranian national norms for 55 kg senior Greco-Roman style wrestling. The measures of bench press and trunk and shoulder flexibility tests were lower than the national norms. In other tests, no major difference was observed between the results of the subject's tests and national norms.